A comparison of the effects of a 4% modified fluid gelatin and a 6% hydroxyethyl starch on haemodilution, colloid osmotic pressure, haemostasis and renal parameters in healthy ponies. (28th July 2016) - Gratwick, Z.; Viljoen, A.; Page, P. C.; Goddard, A.; Fosgate, G. T.; Lyle, C. H.
Summary: Reasons for performing study: Adverse effects on renal health and haemostasis have been documented in human patients administered hydroxyethyl starches (HESs). Gelatins may represent useful substitutes should similar adverse effects be identified in horses. Objectives: To compare the effects of a 4% modified fluid gelatin (MFG) with a 6% (130/0.4) HES on haemodilution, colloid osmotic pressure (COP), haemostasis and renal parameters in healthy ponies. Study design: Randomised crossover experiment. Methods: Three treatments (Treatment A: 10 ml/kg bwt HES; Treatment B: 10 ml/kg bwt MFG; Treatment C: 20 ml/kg bwt MFG) were administered to 6 healthy ponies with a 1 week washout period between treatments. Haematocrit, platelet count, total serum protein, COP, thromboelastography (TEG), prothrombin time (PT), activated partial thromboplastin time (aPTT) and fibrinogen concentration were measured at baseline and at multiple time points up to 24 h post‐infusion. Serum creatinine concentration, urine specific gravity (USG), urine protein:creatinine ratio (UPC), urine γ‐glutamyltransferase:creatinine ratio (UGC) and urine sediment examination (USE) were performed before and at 24 h after each treatment, as well as at 1 week after the final treatment. Results: All treatments resulted in significant haemodilution and increases in COP. Treatment C had a significantly greater effect on haematocrit than the other treatments. The platelet count decreased with all treatments and was significantly lower following Treatment C compared with Treatment B. No clinically relevant differences were observed in any of the TEG parameters within or between treatments. No significant differences in PT, aPTT or fibrinogen concentration were observed among treatments. Serum creatinine concentration, UPC and UGC did not change significantly between pre‐ and post‐study measurements. USG and USE remained within normal limits. Conclusions: Modified fluid gelatin could be considered as an alternative to HES for volume expansion and oncotic support. Neither MFG nor HES were associated with clinically significant adverse effects on haemostasis or renal parameters.